The slow decay and quick revival of self-deception - Chance, Zoë; Gino, Francesca; Norton, Michael I.; Ariely, Dan (Frontiers in Psychology, 2015)
People demonstrate an impressive ability to self-deceive, distorting misbehavior to reflect positively on themselves—for example, by cheating on a test and believing that their inflated performance reflects their true ability. But what happens to self-deception when self-deceivers must face reality, such as when taking another test on which they cannot cheat? We find that self-deception diminishes over time only when self-deceivers are repeatedly confronted with evidence of their true ability (Study 1); this learning, however, fails to make them less susceptible to future self-deception (Study 2).